Estrategias de planificación turística y las funciones participativas de los stakeholders en la Provincia de los Ríos - Zavala Santana, Alicia Maria (2021)
Tourism planning and the participatory functions of stakeholders have been playing a very important role in the tourism sector since thanks to these agents we can involve both the public and private sectors, they are very useful for strengthening tourism in the province of Los Ríos as a national tourist attraction and why not say international. In this project we will work together with both primary and secondary stakeholders as this will help us for an optimal tourism strategy planning in this project to be carried out.